2014
DOI: 10.1007/s13595-014-0409-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Swiss forests to management and climate change in the last 60 years

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
2
14
0
2
Order By: Relevance
“…Similarly, the path analysis indicates that thermophilization and drying are not mere artifacts from an increase in disturbance gaps, rendering sites more open to radiation and soil warming, but independent drivers of compositional changes in the herb layer. This confirms the results of previous works (Hedwall & Brunet, ; Küchler et al., ; Lenoir, Gégout, Dupouey, Bert, & Svenning, ; Savage & Vellend, ) which found indications of a climate driven floristic change in the understory of European forests. Canopy closure due to decreasing tree harvest and tree aging, which has the potential to buffer thermophilization of forest floor vegetation (De Frenne et al., ), is less significant in the study area because mature forest stands, where canopy closure is near its maximum level, predominate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, the path analysis indicates that thermophilization and drying are not mere artifacts from an increase in disturbance gaps, rendering sites more open to radiation and soil warming, but independent drivers of compositional changes in the herb layer. This confirms the results of previous works (Hedwall & Brunet, ; Küchler et al., ; Lenoir, Gégout, Dupouey, Bert, & Svenning, ; Savage & Vellend, ) which found indications of a climate driven floristic change in the understory of European forests. Canopy closure due to decreasing tree harvest and tree aging, which has the potential to buffer thermophilization of forest floor vegetation (De Frenne et al., ), is less significant in the study area because mature forest stands, where canopy closure is near its maximum level, predominate.…”
Section: Discussionsupporting
confidence: 92%
“…This allows the study of compositional vegetation changes and to examine their possible environmental drivers. Some studies found evidence that forest floor vegetation has already responded to increasing temperatures (Küchler, Küchler, Bedolla, & Wohlgemuth, ; Lenoir, Gégout, Marquet, de Ruffray, & Brisse, ; Savage & Vellend, ). Several studies observed responses to increased soil N availability due to N deposition (Bernhardt‐Römermann et al., ; Brunet, Diekmann, & Falkengren‐Grerup, ; Diekmann, Brunet, Rühling, & Falkengren‐Grerup, ; Keith, Newton, Morecroft, Bealey, & Bullock, ; Naaf & Kolk, ; Reinecke et al., ; Thimonier, Dupouey, Bost, & Becker, ) and to acid rain (Diekmann et al., ; Hédl, ; Thimonier et al., ), while others report recovery from acidification in recent years (Reinecke et al., ; Vanhellemont, ).…”
Section: Introductionmentioning
confidence: 99%
“…The forests close to the tree line are more open than the low-elevation forests and therefore profit from a mix of open grassland and forest species, increasing local SR. It is therefore likely that the warming and upslope migration of forest species will lead to a densification of the forest stands at higher elevations (Bodin et al, 2013;Küchler, Küchler, Bedolla, & Wohlgemuth, 2015), accentuated by pasture abandonment , leading to a reduction in SR in the longer term (Dullinger, Dirnbock, & Grabherr, 2004). Because forest plants seem to have difficulties to track their climate niche in geographic space (Bertrand, Lenoir, et al, 2011;Lenoir et al, 2008) and tree growth at the timber line is slow, there might be a considerable time-lag until the effects of forest densification are visible .…”
Section: Changes In Species Richnessmentioning
confidence: 99%
“…The faster recovery may result from lower competition after the cessation of disturbances (Suttle et al 2007) and reduced abiotic stress (e.g. more benign temperatures) at low elevations (Vittoz et al 2009, Küchler et al 2015. Additionally, the faster natural recovery of forests may be attributable to the seeds of low-elevation species generally recruiting faster than high-elevation ones (Kueppers et al 2017).…”
Section: Temporal and Elevational Patterns Of Forest Recoverymentioning
confidence: 99%